Influence of Polymorphic Gene Variants of the Dopaminergic System on the Risk of Disorders with Depressive Symptoms - Rafikova, E. I.; Shibalev, D. V.; Shadrina, M. I.; Slominsky, P. A.; Guekht, A. B.; Ryskov, A. P.; Vasilyev, V. A. (Russian journal of genetics, 2021)
Depression is characterized by extremely high clinical heterogeneity. Only a few of the many symptoms of depression may overlap in different people with major depressive disorder. The search for molecular genetic markers of depression often yields conflicting results, which may be due to the heterogeneity of the samples. The aim of this work was to identify genetic risk factors for three diseases characterized by severe depressive symptoms. All participants were of East Slavic origin from Moscow and the regions of Central Russia. The polymorphisms of the genes of the dopamine transporter ( SLC6A3/DAT1 ), dopamine receptors ( DRD4 and DRD2 ), and the enzyme catechol- O -methyltransferase ( COMT ) were studied in patients with three diagnoses: depressive episode, recurrent depression, and mixed anxiety and depressive disorder. We observed statistically significant differences in the distribution of alleles for the SLC6A3 ( DAT1 ) 40 bp VNTR locus in patients with mixed anxiety and depressive disorder. The short allele ( 8R and 9R ) was more common in patients than in the control group ( p = 0.005); significant differences were also observed in the distribution of genotypes of this locus ( p = 0.025). No associations were found between the loci of the dopaminergic system and the risk of depressive episode and recurrent depression.